2015
DOI: 10.1016/j.cellsig.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Growth-factor dependent expression of the translationally controlled tumour protein TCTP is regulated through the PI3-K/Akt/mTORC1 signalling pathway

Abstract: Translationally controlled tumour protein TCTP (gene symbol: TPT1) is a highly-conserved, cyto-protective protein implicated in many physiological and disease processes, in particular cancer, where it is associated with poor patient outcomes. To understand the mechanisms underlying the accumulation of high TCTP levels in cancer cells, we studied the signalling pathways that control translation of TCTP mRNA, which contains a 5'-terminal oligopyrimidine tract (5'-TOP). In HT29 colon cancer cells and in HeLa cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 72 publications
5
47
0
Order By: Relevance
“…Recently, we (Bommer et al 2017) and a Chinese group (Xiao et al 2016) demonstrated that indeed TCTP levels (assessed by immunohistochemistry) increase early in CRC, already at the adenoma stage. This is consistent with our finding that during growthinduction of both HeLa cells and HT29 colon cancer cells, TCTP synthesis is translationally up-regulated through the PI3K/Akt/mTORC1 signalling pathway (Bommer et al 2015), given the earlier observation that this pathway is activated early in the development of colorectal cancer (Zhang et al 2009). Epithelial-to-mesenchymal transition (EMT) of cancer cells is a crucial step in the development of invasiveness and metastasis of tumours.…”
Section: Mechanistic Involvement In Cancer Progressionsupporting
confidence: 92%
See 4 more Smart Citations
“…Recently, we (Bommer et al 2017) and a Chinese group (Xiao et al 2016) demonstrated that indeed TCTP levels (assessed by immunohistochemistry) increase early in CRC, already at the adenoma stage. This is consistent with our finding that during growthinduction of both HeLa cells and HT29 colon cancer cells, TCTP synthesis is translationally up-regulated through the PI3K/Akt/mTORC1 signalling pathway (Bommer et al 2015), given the earlier observation that this pathway is activated early in the development of colorectal cancer (Zhang et al 2009). Epithelial-to-mesenchymal transition (EMT) of cancer cells is a crucial step in the development of invasiveness and metastasis of tumours.…”
Section: Mechanistic Involvement In Cancer Progressionsupporting
confidence: 92%
“…Typically, we observed a four-fold increase of TCTP levels after serum-stimulation of mammalian cells (Bommer et al 2002(Bommer et al , 2015. The involvement of TCTP in cellular growth regulation is documented in various settings.…”
Section: Tctp and Cell Growth Regulationmentioning
confidence: 85%
See 3 more Smart Citations